A genome-wide association study identified one variant associated with static spatial working memory in Chinese population - Zhang, Liming; Zhu, Zijian; Yang, Qing; Zhao, Jingjing (Frontiers in Genetics, 2022)
Spatial working memory (SWM) is a kind of memory that temporarily preserves spatial information (the location or order of objects, etc.). Individuals with mental disorders tend to show worse performance in SWM task. This study investigated the genetic basis of two subtypes of SWM, static spatial working memory (SSWM) and dynamic spatial working memory (DSWM) in humans, using quantitative genomic analyses. A total of 451 Chinese students were tested on their magnitudes of SSWM and DSWM. A genome-wide association study (GWAS) was performed. Two SNPs (top SNP: rs80263879, p=1.6×10-9, gene: epoxide hydrolase 2, EPHX2) reaching genome-wide significance for SSWM were identified. There is a high linkage disequilibrium between these two SNPs. The data of expression quantitative trait locus (eQTL) showed that different genotypes of rs80263879 and rs72478903 made significant differences in the expression of EPHX2 gene in the spinal cord (p=0.022, p=0.048). Enrichment analysis identified a gene set significantly associated with DSWM. Overall, our study discovered a candidate genetic locus and gene set for the genetics of the SWM.